Mathematıcal reasoning and proof in fıfth grade mathematıcs textbook - ŞENGÜL, SARE (My University, 2022)
Science confirms by observation, mathematics by reasoning, and the essence of mathematics lies in proofs. Creating valid arguments or proofs and criticizing arguments are integral parts of doing math. Mathematics is a science based on concepts and operations with a certain order and logical order. To discover and make sense of this order is to do mathematics. For this reason, it can be said that school mathematics should provide students with opportunities to explore and make sense of it. In order for students to take advantage of these opportunities, we can say that mathematics learning environments should provide students with mathematical reasoning and proof skills. Analyzing the reasoning and proving activities in textbooks, one of the factors that affect mathematics teaching and learning, is the first important step to understanding the opportunities for students to learn to reason and prove. This research examines a fifth-grade mathematics textbook presented to all students by the Ministry of National Education through the Education Informatics Network in the context of activities for mathematical reasoning and proof. In the analysis of the mathematics textbook, the analytical framework developed by the researchers based on the evaluation criteria in the studies of Stylianides (2008, 2009) and Thompson et al. (2012) is used for data analysis. In this context, reasoning and proof activities are evaluated separately according to the secondary school fifthgrade mathematics learning areas, the activities in the chapters of the book and the purposes of the activities. The analysis process continues according to the purposes of reasoning and proof activities and the types of arguments the students can create.
Keywords: Reasoning and proof; mathematics; textbook analysis